2021
DOI: 10.1111/jvs.12995
|View full text |Cite
|
Sign up to set email alerts
|

Fire‐triggered flowering is the dominant post‐fire strategy in a tropical savanna

Abstract: Questions:In fire-prone ecosystems, fire can enhance the flowering and fruiting of many species, a strategy assumed to be well represented in savanna. Despite this, there are surprisingly few studies assessing how prevalent fire-stimulated flowering is. Thus, we asked: (a) are there differences in the reproductive phenology of Cerrado plants between recently burned and unburned areas; (b) how does fire affect the speed of flowering and how does this differ between growth forms; and (c) what are the post-fire f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 52 publications
4
44
1
1
Order By: Relevance
“…Fire appears to stimulate flowering in many plant species in fire‐prone habitats (Ehrenreich & Aikman, 1963; Pemble et al ., 1981; Hartnett, 1990; Peter, 2002a,b; Pilon et al ., 2018; Zirondi et al ., 2021), as we found in L . aspera (Table 1).…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Fire appears to stimulate flowering in many plant species in fire‐prone habitats (Ehrenreich & Aikman, 1963; Pemble et al ., 1981; Hartnett, 1990; Peter, 2002a,b; Pilon et al ., 2018; Zirondi et al ., 2021), as we found in L . aspera (Table 1).…”
Section: Discussionsupporting
confidence: 84%
“…We suspect that fire affects S. speciosa differently than L. aspera in part because S. speciosa is more likely to flower each year and produces stems every year regardless of flowering status, whereas L. aspera flowers infrequently with drastic differences in aboveground structure and biomass between vegetative and flowering years. Fire appears to stimulate flowering in many plant species in fire-prone habitats (Ehrenreich & Aikman, 1963;Pemble et al, 1981;Hartnett, 1990;Peter, 2002a,b;Pilon et al, 2018;Zirondi et al, 2021), as we found in L. aspera (Table 1). Synchronized flowering, which we conceptualize as a continuous trait, at least in perennial prairie species, may be an adaptive trait, as posited for masting species (Janzen, 1971;Bogdziewicz et al, 2020Bogdziewicz et al, , 2021Kelly, 2021).…”
Section: New Phytologistsupporting
confidence: 75%
See 2 more Smart Citations
“…Grasses also respond very fast to dry‐season fires by resprouting and allocating reserves to flowering, with their flowering peak being just 30 days post fire, with ca. 30% of the species only flowering when fire occurs (Zirondi et al, 2021). However, such studies analyzed post‐fire grass flowering only after dry‐season fires and information is still lacking about the effects of fire given different seasons, on grass phenology.…”
Section: Introductionmentioning
confidence: 99%